Implementation research and human-centred design: how theory driven human-centred design can sustain trust in complex health systems, support measurement and drive sustained community health volunteer engagement. (6th November 2020) - Adam, Mary B; Minyenya-Njuguna, Joy; Karuri Kamiru, Wilson; Mbugua, Simon; Makobu, Naomi Wambui; Donelson, Angela J
Abstract: Human-centred design (HCD) can support complex health system interventions by navigating thorny implementation problems that often derail population health efforts. HCD is a pragmatic, 'practice framework', not an intervention protocol. It can build empathy by bringing patient voice, user perspective and innovation to construct and repair pieces of the intervention or health system. However, its emphasis on product development and process change with fixed end points has left it as an approach lacking explanatory power and reproducible measurement. Yet when informed by theory, the tremendous innovation potential of HCD can be harnessed to drive sustainability, mediate implementation problems, frame measurement constructs and ultimately improve population-level health outcomes. In attempting to mine, the potential of HCD we move beyond the pragmatic 'how it works', to the theoretical question, 'why it works'. In doing so, we explore a more fundamental human question, 'How can participation and engagement be sustained for impact in close to the community health systems?' In this exploration, we illustrate the power of HCD by linking it to our theory of trust building. The research method we utilize is that of a longitudinal process evaluation. We leverage the heterogeneity of five community health units from the diverse setting (rural, peri-urban slum) to better understand what works for whom and in what context by tracking 21 groups of community health volunteers (CHVs) over 12 months. We report results with a focus on the outlier case failure to illustrate the contrast with common features of sustained CHV engagement, where recurrent reciprocal cycles of trust building are demonstrated in the successful implementation of action plans in plan-do-study-act cycles for improvement. All was accomplished by CHVs with no external funding. We conclude by discussing how HCD could be unleashed if linked to theoretical frameworks, increasing ability to address implementation challenges in complex health systems.